Land resources of the Zvenigorod district of Cherkasy region: assessment of the state and optimization - Bavrovska, N.; Shlikhta, T. (Land Management, Cadastre and Land Monitoring, 2019)
The article presents a comparative analysis of the optimal environmental parameters and the current structure of lands in the Zvenigorod district of Cherkasy region.The purpose of the study is to assess the current state of land use in the Zvenigorod district of Cherkasy region and to identify problems and justify ways of solving it.An analysis of the current state of land use in the district indicates a high level of technological load on land resources, which results in low ecological stability of land use in general.An assessment of ecological stability of the territorial structure land of the district and sustainability of lands to anthropogenic load is provided. In the result of carrying out researchesкey directions in the optimization of territorial land use in the Zvenigorod district are grounded: reduction of the area of arable low-yielding lands due to their withdrawal from arable land and transfer to hay-grazing lands; increasing the area of protective forest belt in the cultivated territories to 5-7%.